Hydrolyzable tannins in local Thai plants: Potential applications as poultry feed supplements: A systematic review - Tanakamol Mahawan; Pornchai Pornpanom; Surya Nur Rahmatullah; Tuempong Wongtawan; Thotsapol Thomrongsuwannakij (Veterinary World)
Background and Aim: The global shift toward antibiotic-free poultry production necessitates sustainable alternatives to conventional growth promoters. Hydrolyzable tannins (HTs) from plants have shown antimicrobial, antioxidant, and gut-modulatory effects, making them promising feed additives. However, reliance on imported tannins from temperate species limits access for tropical producers, especially in Thailand. This study aimed to systematically evaluate locally available Thai plant species as alternative sources of HTs for poultry feed, with a focus on their biological activities, economic feasibility, and practical integration potential.